القانون الدولي، وسياسة التسلح النووي في الشرق الأوسط - زينب, سعد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The appendance of nuclear weapon formed a coup center in the evolution of the modern history of this weapon. A weapon of mass destruction, which did not change the characteristics of military actions as well as the art of leadership of the war and world peace. The principle of self – restraint, one of the most important concepts of strategic nuclear idioms. The strategy of the two superpowers during the "cold war" identified the possession of the conditions for restraint in relations between these two countries. The theory of self-restraint led to attempts to stay away of using the weapon of mass destruction. Despite of this the appendance of the idea of the possibility to use this weapon in order to prevent the other party to use it. The determination of the role and importance of the "unclear factor" in the middle east in general and The Zionist occupation state foreign policy strategy in specific proceeding from this the show of the mutual relations between the forms of the principles of The Zionist occupation state strategy to create conditions of war "traditional and nuclear" in the Middle East. International and national importance. Where the future of the unclear weapons in the middle east and the serious progress that has happened as a result of the change in the The future of the nuclear weapons in the Middle East and the serious progress that has happened as a result of the change in the political leadership in the region and which is the result of the deep changes in the system of international changes reflected on the process of the formation and implementations of policy, military strategy for the region. if the nuclear weapons exist at the Arabs this could accelerate the process of reaching a just and comprehensive peace in the Middle East. After that it is possible to talk about the establishment of zones free of nuclear weapon. The analysis of The Zionist occupation state unclear weapon which was formed in conditions of solving the Middle East crisis, the possibility of changing the position of The Zionist occupation state unclear practicality possible "nuclear reality" will present in the system of international relations in the Middle East. إنّ ظهور السلاح النووي، شكل مركز انقلاب، في تطور التاريخ المعاصر. هذا السلاح، سلاح الدمار الشامل، الذي لم يغير صفات الأعمال العسكرية بل، وكذلك فن قيادة الحرب، والسلم العالميين. مبدأ ضبط النفس – واحد من أهم مفاهيم مصطلحات الاستراتيجية النووية، استراتيجية الدولتين العظميين في فترة "الحرب الباردة" حددت امتلاك الظروف "لضبط النفس في العلاقات بين هاتين الدولتين. نظرية "ضبط النفس" أدت إلى محاولات الابتعاد عن استخدام سلاح الإبادة الشاملة، ومع هذا فإن ظهور فكرة إمكانية استخدام هذا السلاح بهدف منع استخدامه من الطرف الآخر. ويلعب العامل النووي دوراً هاماً في تشكيل الظروف السياسية في الشرق الأوسط عموماً، واستراتيجية السياسة الخارجية لدولة الاحتلال الصهيوني خصوصاً. وانطلاقاً من هذا، فإن أهمية لإظهار الصلات المتبادلة بين أشكال مبادئ استراتيجية دولة الاحتلال الصهيوني، لتكوين ظروف نشوب حرب "تقليدية" و"نووية" في الشرق الأوسط ، حيث إن مستقبل السلاح النووي في الشرق الأوسط، وكذلك التقدم الجدي الذي حصل نتيجة التغير في القيادة السياسية في المنطقة الحاصل نتيجة التغيرات العميقة في نظم العلاقات الدولية، انعكسا على عملية تشكيل وتطبيق استراتيجية السياسة العسكرية لدول المنطقة. لو كان السلاح النووي موجوداً عند العرب، لكان بالإمكان تسريع عملية الوصول إلى السلام العادل والشامل في الشرق الأوسط، بعد ذلك من الممكن الحديث عن إقامة مناطق خالية من السلاح النووي. إن تحليل "السياسة النووية لدولة الاحتلال الصهيوني" التي تشكلت في ظروف حل أزمة الشرق الأوسط، يوضح أن إمكانية تغيير موقفها النووي عملياً غير ممكن، حيث أن "الواقع النووي" سيحضر في نظام العلاقات الدولية في منطقة الشرق الأوسط".